2015
DOI: 10.1111/bjd.14077
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the maintenance of response during systemic antipsoriatic therapy

Abstract: As a chronic disease psoriasis often requires long-term treatment. Successful continuation of therapy during a maintenance phase is therefore important. A systematic review was performed on the efficacy of psoriasis drugs during maintenance treatment in patients who had achieved sufficient treatment success during the induction period. Maintenance therapy is defined as treatment during the period after successful induction therapy. Inclusion criteria were prospective studies with systemic therapies recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Overall, ixekizumab had an acceptable long‐term safety profile with no new safety findings, which is consistent with that reported previously . Patients with moderate‐to‐severe psoriasis usually require long‐term treatment to achieve disease control . Rare diseases such as cardiovascular disorders or diseases with long‐term latency such as malignancy are potential risks for patients with psoriasis and its treatment .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, ixekizumab had an acceptable long‐term safety profile with no new safety findings, which is consistent with that reported previously . Patients with moderate‐to‐severe psoriasis usually require long‐term treatment to achieve disease control . Rare diseases such as cardiovascular disorders or diseases with long‐term latency such as malignancy are potential risks for patients with psoriasis and its treatment .…”
Section: Discussionsupporting
confidence: 86%
“…1,2,5 Patients with moderate-tosevere psoriasis usually require long-term treatment to achieve disease control. [6][7][8][9] Rare diseases such as cardiovascular disorders or diseases with long-term latency such as malignancy are potential risks for patients with psoriasis and its treatment. [10][11][12][13][14][15][16] It is noteworthy that in this analysis, long-term ixekizumab exposure up to 156 weeks was not associated with an increased risk of cardiovascular disorders and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Per the Italy guidelines and those established by the American Academic of Dermatology (AAD), CsA is optimally used as intermittent therapy and courses can be repeated at intervals 9,11 . Several studies have compared the two kinds of therapies; however, it is uncertain whether there is any difference between their success rates 14 . Ozawa et al found that continuous monotherapy seemed to be more clinically useful compared to intermittent therapy for the following reasons: (a) the time required to achieve remission tended to be longer with intermittent therapy, while no change was observed with continuous monotherapy; (b) the time until relapse tended to become shorter with both treatment methods; however, this tendency was more marked with intermittent therapy; and (c) evaluation for prognosis with averaged PASI (E‐PAP) was lower in the continuous monotherapy group and the patients were more satisfied 15 .…”
Section: Cyclosporinementioning
confidence: 99%
“…A further SR aimed to evaluate long‐term treatment success through the assessment of rates of maintaining treatment response after successful induction therapy with either systemic or biologic therapy for patients with psoriasis . However, high‐quality data on ustekinumab therapy were omitted because patients in Phase III studies were re‐randomized following induction at 9 months rather than the authors’ chosen cut‐off of 6 months.…”
Section: Maintenance Of Response To Systemic and Biologic Treatmentsmentioning
confidence: 99%